HIF2A and IGF2 Expression Correlates in Human Neuroblastoma Cells and Normal Immature Sympathetic Neuroblasts - Mohlin, Sofie (Neoplasia Press Inc., 2013)
During normal sympathetic nervous system (SNS) development, cells of the ganglionic lineage can malignantly transform and develop into the childhood tumor neuroblastoma. Hypoxia-inducible transcription factors (HIFs) mediate cellular responses during normal development and are central in the adaptation to oxygen shortage. HIFs are also implicated in the progression of several cancer forms, and high HIF-2α expression correlates with disseminated disease and poor outcome in neuroblastoma. During normal SNS development, HIF2A is transiently expressed in neuroblasts and chromaffin cells. SNS cells can, during development, be distinguished by distinct gene expression patterns, and insulin-like growth factor 2 (IGF2) is a marker of sympathetic chromaffin cells, whereas sympathetic neuroblasts lack IGF2 expression. Despite the neuronal derivation of neuroblastomas, we show that neuroblastoma cell lines and specimens express IGF2 and that expression of HIF2A and IGF2 correlates, with the strongest correlation in high-stage tumors. In neuroblastoma, both IGF2 and HIF2A are hypoxia-driven and knocking down IGF2 at hypoxia resulted in downregulated HIF2A levels. HIF-2α and IGF2 were strongly expressed in subsets of immature neuroblastoma cells, suggesting that these two genes could be co-expressed also at early stages of SNS development. We show that IGF2 is indeed expressed in sympathetic chain ganglia at embryonic week 6.5, a developmental stage when HIF-2α is present. These findings provide a rationale for the unexpected IGF2 expression in neuroblastomas and might suggest that IGF2 and HIF2A positive neuroblastoma cells are arrested at an embryonic differentiation stage corresponding to the stage when sympathetic chain ganglia begins to coalesce.